2021
DOI: 10.3390/healthcare9040443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Practice of Preventive Behaviors and the Fear of COVID-19 among Dentists in Oradea Metropolitan Area after the First Wave of Pandemic; a Cross-Sectional Study

Abstract: Dental clinics were suspected to be a hotspot for nosocomial transmission of COVID-19 due to the easy spread of the virus. The study investigated the preventive behaviors applied in dentistry settings and the level of fear of COVID-19 infection among dentists. A total of 83 respondents (34.94% male and 63.86% female) were included in the research. Sociodemographic data were collected, together with new institutional and personal rules regarding preventive behaviors. Fear of COVID-19 Scale was used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…In light of national COVID-19 infection-control recommendations, dental faculties had to suspend in-person instruction, and teaching activity was conducted online. Some researchers who focused on online dental education pointed out the rapid change adopted by dental faculties in many countries, such as the USA [ 6 , 7 , 8 , 9 ], Germany [ 10 ], Italy [ 11 ], China [ 12 , 13 ], Chile [ 14 ], Brazil [ 8 , 15 , 16 ], Pakistan [ 17 ], Nepal [ 18 , 19 ], Indonesia [ 20 ], India [ 21 , 22 ], Jordan [ 23 ], Romania [ 24 , 25 , 26 ], Portugal [ 27 , 28 ], Cyprus [ 29 ], Australia [ 8 , 30 ], and Spain [ 31 ]. During the first year of the pandemic, the academic research teams additionally wanted to identify the differences between countries in what aspects of dental education were disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…In light of national COVID-19 infection-control recommendations, dental faculties had to suspend in-person instruction, and teaching activity was conducted online. Some researchers who focused on online dental education pointed out the rapid change adopted by dental faculties in many countries, such as the USA [ 6 , 7 , 8 , 9 ], Germany [ 10 ], Italy [ 11 ], China [ 12 , 13 ], Chile [ 14 ], Brazil [ 8 , 15 , 16 ], Pakistan [ 17 ], Nepal [ 18 , 19 ], Indonesia [ 20 ], India [ 21 , 22 ], Jordan [ 23 ], Romania [ 24 , 25 , 26 ], Portugal [ 27 , 28 ], Cyprus [ 29 ], Australia [ 8 , 30 ], and Spain [ 31 ]. During the first year of the pandemic, the academic research teams additionally wanted to identify the differences between countries in what aspects of dental education were disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study conducted by these authors, the rate of dentists diagnosed with COVID-19 was 1.7% [17]. In the study of Iurcov et al, it was thought that the positive rate was low because the participants did not take patients [30]. In the current study, the number of dentists who stated that they did not receive patients from the start of the outbreak until the time of this study was only five.…”
Section: Discussionmentioning
confidence: 45%
“…According to the Turkish Dental Association, 32 dentists have died since the beginning of the outbreak [29]. In a study on fear and preventive behaviors caused by the COVID-19 outbreak in dentists, 3.9% of dentists who participated in the study confirmed that they were COVID-19-positive [30]. In a study conducted by Sebastian et al [31], the positive rate of dentists was 4%, and in the study of Alajmi et al [32], this rate was also 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Another medical speciality extremely touched by the pandemic was dentistry, with a high risk of infection. A quarter of the dentists included in the research by Iurcov et al [ 69 ] declared that they had periods when they lived away from home, being afraid of transmitting the disease to their family members; this especially applied to doctors with children. Dentists with chronic diseases showed a higher level of anxiety when following the news and stories related to COVID-19 on TV, the media, or social networks.…”
Section: Discussionmentioning
confidence: 99%